Investigating Students' Learning Experiences in a Neural Engineering Integrated STEM High School Curriculum - Tugce Aldemir; Ido Davidesco; Susan Meabh Kelly; Noah Glaser; Aaron M. Kyle; Bianca Montrosse-Moorhead; Katie Lane (MDPI AG, 2022)
STEM integration has become a national and international priority, but our understanding of student learning experiences in integrated STEM courses, especially those that integrate life sciences and engineering design, is limited. Our team has designed a new high school curriculum unit that focuses on neural engineering, an emerging interdisciplinary field that brings together neuroscience, technology, and engineering. Through the implementation of the unit in a high school engineering design course, we asked how incorporating life sciences into an engineering course supported student learning and what challenges were experienced by the students and their teacher. To address these questions, we conducted an exploratory case study consisting of a student focus group, an interview with the teacher, and analysis of student journals. Our analysis suggests that students were highly engaged by the authentic and collaborative engineering design process, helping solidify their self-efficacy and interest in engineering design. We also identified some challenges, such as students' lower interest in life sciences compared to engineering design and the teacher lacking a life sciences background. These preliminary findings suggest that neural engineering can provide an effective context to the integration of life sciences and engineering design but more scaffolding and teacher support is needed for full integration.